An overview of energy efficiency standards in China's transport sector. (January 2017) - Hao, Han; Liu, Zongwei; Zhao, Fuquan
Abstract: China's transport sector is facing severe energy and environmental challenges. Establishing energy efficiency standards is an essential measure to cope with these challenges. This paper comprehensively reviews the energy efficiency standards in China's road, water, aviation, railway and pipeline transport sectors. Based on the review, it is suggested that (1) the integrity of policy framework should be further improved. Energy efficiency standards-based market access qualification mechanism is quite necessary for all transport sectors, especially the aviation, railway and pipeline transport sectors, where such mechanism is absent. (2) Efforts for improving energy efficiency should be balanced among different transport sectors. Priority should be determined by considering each sector's energy consumption, the cost and potential of energy efficiency improvement, etc. Especially, the major energy-consuming sectors, such as heavy-duty vehicles should have similar priority to passenger vehicles in the overall energy efficiency improvement scheme. (3) The scientific basis for the energy efficiency standards should be enhanced. Policies should be proposed with full considerations of China's context, rather than borrowing the experiences of developed countries. Intelligence from the research community should be incorporated to ensure the rationality of the policies.